E-025 Insular infarction at presentation and total infarct growth rate over 48 hours in large vessel occlusion stroke. (23rd July 2022) - Regenhardt, R; Singhal, A; He, J; Gonzalez, G; Lev, M
Abstract : Introduction: Understanding infarct growth rate (IGR) is key to identifying patients with slow progressing large vessel occlusion (LVO) stroke that may benefit from delayed endovascular thrombectomy (EVT). We hypothesized that the extent of presentation insular ribbon infarction was associated with IGR up to 48 hours after presentation. Methods: Patients with LVO who underwent ≥3 MRIs over 48hr in a clinical trial before EVT became standard of care (2007–2009) were included. Percent insular ribbon infarction (PIRI) score was calculated from DWI and ADC: 0 - 0% infarction, 1 - 25%, 2 - 50%, 3 - 75%, 4 - 100%. Results: Among 31 patients, 39% were female and median age was 71. LVO location was the ICA (23%), M1 (42%), and M2 (36%). PIRI scores were 0 (26%), 1 (10%), 2 (13%), 3 (16%), and 4 (35%). Median onset-to-presentation IGR was different comparing PIRI scores: 0.93, 5.42, 4.69, 14.19, 22.07 (cc/h, p=0.001). Furthermore, presentation-to-48-hour IGR (p=0.005), absolute presentation infarct volume <0.0001), and 90-day FLAIR infarct volume (p=0.02) were different. 90-day mRS ≤2 was also different: 86%, 33%, 67%, 20%, 0% (p=0.003). In multivariable models controlling for age, LVO location, and collaterals, PIRI was associated with onset-to-presentation IGR (βadj=0.88; 95%CI=0.28, 1.48; p=0.004), presentation-to-48 hour IGR (βadj=0.77; 95%CI=0.17, 1.38; p=0.01), absolute presentation infarct volume (βadj=1.42; 95%CI=0.71, 2.13; p<0.001), presentation-to-48 hour infarct growth (βadj=0.67; 95%CI=0.07, 1.27; p=0.03), and reduced 90-day mRS ≤2 (aOR=0.33; 95%CI=0.14, 0.97; p=0.01). Conclusions: In this unique dataset of LVO patients untreated with reperfusion therapies, PIRI was strongly associated with infarct growth up to 48 hours and long-term outcomes. PIRI may help guide management for EVT in the delayed window, especially when there are delays to treatment such as those related to patient transfer. Disclosures: R. Regenhardt: None. A. Singhal: None. J. He: None. G. Gonzalez: None. M. Lev: None.